G-SAVE 공법 탑재 차량의 예비위험성평가 - 정의필(Ui Pil Chong); 박현철(Hyun Chul Park); 박영수(Young Soo Park); 안병철(Byung Chul Ahn); 한덕수(Deok Soo Han); 전현준(Hyeon Jun Jeon) (Biuletyn Uniejowski, 2023)
The structures for road safety are guard rails that protect the cars and passengers. If an accident occurs on the roads after a long period of installation, it may escalate into a major disaster. In order to repair many guard rails, the existing repair method of replacing them with new ones requires enormous financial resources. To solve this problem, the G-SAVE method was developed to repair the guard rail without replacing them. This method removes the rust on the surface of the guard rail and then performs ambient-dip galvanizing coating on it without replacing the new ones. No studies or reports have yet been made on the risk assessment of harmful substances, vehicles for these entire processes. Therefore, this paper focuses on risk assessment using the PHA (Preliminary Hazard Analysis) technique and conducts risk assessment for concept design stage of the coating vehicles.